Study of co-infection of Malaria and Dengue with COVID-19. - Shrestha, Padma (2021)
Abstract: The coronavirus infection 2019 (COVID-19) is an ongoing pandemic disease affecting more than 224 million cases worldwide with total deaths exceeding 4.6 million deaths. COVID-19 presents with many non-specific symptoms such as fever, cough, fatigue, shortness of breath, headache and myalgia, that may overlap with vector-borne diseases, such as dengue and malaria. Co-infection with malaria and dengue in endemic regions might be of high clinical importance as the pandemic continues to spread. Our study is designed to detect the malaria and dengue infections in febrile/symptomatic patients suspected of COVID-19 which will help public, health professional and health sector to find out malaria and dengue co-infections with SARS-CoV-2 and subsequently their role in the COVID-19 clinical outcomes and management. A prospective study was conducted among febrile/symptomatic patients suspected of COVID-19 visiting STIDH. One hundred and twenty-three patients suspected of COVID-19 were investigated for rapid malaria and dengue tests in association with COVID-19. During two months period, out of 64 COVID-19 positive patients, 5 patients were expired while 3 patients who had severe COVID-19 pneumonia were in the Ventilator and the condition was not good. The condition of four patients were improving but still in the hospital till completion of our research work. Majority of patients were discharged from the hospital ranging from 2 days upto one month depending on severity of disease. COVID-19 and malaria co-infection was not found in the study. But COVID-19 and dengue coinfection was found in two admitted COVID-19 positive patients. Fever was the common symptom manifested by both co-infected patients. The predominant laboratory results of both patients included neutrophilia, lymphocytopenia, elevated transaminases and elevated serum ferritin. Both co-infected patients were diagnosed on time and recovered after proper treatment without any complications. Though co-infection of COVID-19 and dengue virus is associated with significant morbidity and mortality, timely and correct diagnosis and treatment lead to quick recovery of the patient. The outcome of the study highlights the importance of diagnosis of other diseases which are endemic and can have signs and symptoms like COVID-19 to evaluate the possible co-infections of COVID-19 with other endemic tropical infections particularly in limited-resource countries like Nepal. Key words: COVID-19, malaria, dengue, co-infection, fever